MITIGATION OPTIONS OF GREEN-HOUSE GASES (GHG) FOR AGRICULTURE - A. Karim Makarim; I. Handoko; Irsal Las; M. Yacop; Hidayat Pawitan; Justika S. Baharsjah (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1998)
Abstract is available in the full text (pdf format)